Pemberdayaan Ekonomi Pesantren Melalui Budidaya Lele: Studi Implementasi Program LAZNAS PPPA Daarul Qur’an Jawa Timur di Pesantren Daru Ulil Albab Nganjuk - Nabila Ayu Lestari; Moch. Khoirul Anwar (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This research aims to analyze the effectiveness of the Islamic boarding school (pesantren) economic empowerment program implemented by LAZNAS PPPA Daarul Qur’an East Java through a catfish cultivation business unit at Daru Ulil Albab Pesantren, Nganjuk. The research methodology employed is descriptive qualitative with a phenomenological approach to comprehend the profound experiences of both managers and students (santri). Data collection was conducted through in-depth interviews, direct observation, and documentation. The results demonstrate that the empowerment program is effective and has successfully enhanced the economic independence of the pesantren while equipping students with practical entrepreneurial skills. These findings are based on three primary indicators: First, target accuracy was achieved through the allocation of productive capital in the form of 1,000 catfish fingerlings. Second, program success is reflected in the transformation of a previously failed business unit into a productive one. Third, the adaptation aspect was realized through a structured monitoring system. This study recommends the standardization of routine monitoring schedules and the equal distribution of technical training for all students to ensure the future sustainability of the program.